Age-related differences in acceleration, maximum running speed, and repeated-sprint performance in young soccer players - Mendez-Villanueva, A.; Buchheit, M.; Kuitunen, S.; Douglas, A.; Peltola, E.; Bourdon, P. (Journal of Sports Sciences, 2011)
We investigated age-related differences in the relationships among acceleration, maximum running speed, and repeated-sprint performance in 61 highly trained young male soccer players (Under 14, n = 14; Under 16, n = 22; Under 18, n = 25). We also examined the possible influence of anthropometry (stature, body mass, fat-free mass) and biological maturation (age at peak height velocity) on performance in those three sprint-running qualities. Players were tested for 10-m sprint (acceleration), flying 20-m sprint (maximum running speed), and 10 × 30-m sprint (repeated-sprint performance) times. Correlations between acceleration, maximum running speed, and repeated-sprint performance were positive and large to almost perfect (r = 0.55-0.96), irrespective of age group. There were age-based differences both in absolute performance in the three sprint-running qualities (Under 18 > Under 16 > Under 14; P < 0.001) and when body mass and fat-free mass were statistically controlled (P < 0.05). In contrast, all between-group differences disappeared after adjustment for age at peak height velocity (P > 0.05). The large correlations among acceleration, maximum running speed, and repeated-sprint performance in all age groups, as well as the disappearance of between-group differences when adjusted for estimated biological maturity, suggest that these physical qualities in young highly trained soccer players might be considered as a general quality, which is likely to be related to qualitative adaptations that accompany maturation.